A Deliberation on Jurisprudential Evidences of Article 468 of Islamic Penal Law, Passed in 1392 sh/2013 - Ã™Â…Ã˜ÂÃ™Â…Ã˜Â¯Ã›ÂŒÃ˜Â§Ã™Â†, Ã˜Â¹Ã™Â„Ã›ÂŒ; Ã™Â…Ã˜ÂÃ˜Â³Ã™Â†Ã›ÂŒ Ã˜Â¯Ã™Â‡ÃšÂ©Ã™Â„Ã˜Â§Ã™Â†Ã›ÂŒ, Ã™Â…Ã˜ÂÃ™Â…Ã˜Â¯; Ã™Â‚Ã˜Â¨Ã™ÂˆÃ™Â„Ã›ÂŒ Ã˜Â¯Ã˜Â± Ã˜Â§Ã™ÂÃ˜Â´Ã˜Â§Ã™Â†, Ã™Â…Ã˜ÂÃ™Â…Ã˜Â¯Ã˜ÂªÃ™Â‚Ã›ÂŒ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
By accepting the responsibility of âÄqila (blood relatives of the person perpetrated homicide) in unintentional homicides, the Islamic Penal Law, passed on Ordibehesht 1, 1392 sh/March 21, 2013, has included this view in article 463. This law maintains the following concerning how to pay for the diya (blood money) mentioned under article 468, ââÄqila includes father, son, and the paternal and maternal blood relatives or paternal in order of inheritance level.â The content of the latter article relies on the consent of the renowned majority of the ImÄmÄ« jurists. They believe, âWith the existence of the nearest of kin, undertaking of the farthest of kin is inapplicable and in case of the presence of all the male blood relatives, payment of the blood money is obligatory upon the nearest of kin according to the level of inheritance.â Their main evidence is their relying on the Äya, ï´¾but the blood relatives are more entitled to inherit from one another in the Book of Allahï´¿ as well as the traditions concerning the above-mentioned issue. The writer does not regard as complete the reliance on the above Äya and as fully approved the reliance on traditions. After criticizing the evidences of the generally accepted view, he concludes the following, âIn payment of the blood money for unintentional homicide, the observance of order among the Äqilia is not necessary and all of them are responsible for payment of the blood money; even though they are not heritable at death.â Although contrary to the generally accepted view, this view has drawn the agreement of some of the jurists; moreover, the generalities of the evidences approve it as well.â